2020
DOI: 10.1007/s13762-020-03003-5
|View full text |Cite
|
Sign up to set email alerts
|

Removal of textile dyes from water by jute stick activated carbon: process optimization and isotherm studies

Abstract: In this study, jute stick derived activated carbon (JSAC) has been evaluated as an adsorbent to remove textile dyes namely acid red-1 (AR-1), reactive orange-16 (RO-16), and methylene blue (MB) from water using the Box-Behnken model of response surface methodology (RSM). The direct and interaction effects of four independent process parameters namely solution pH, initial dye concentration, adsorbent dose, and time were investigated and optimized for textile dye by using ANOVA. The optimum conditions for maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Other peaks at JSC 1,377.17 cm À1 (C-N stretching vibration or amine), 1,273.02 cm À1 (vibrations of C-O stretching in alcohols), 987.55 cm À1 (C ¼ C stretching vibration), 844.82 cm À1 (C-H stretching vibration) were observed. Similar types of IR spectrum and functional groups were found by several authors (Chakraborty et al 2020;Ghosh et al 2021aGhosh et al , 2021b. The presence of a porous and uneven surface was indicated by using SEM analysis, which might have played a substantial role in providing high surface area and huge space for active sites (Figure 2).…”
Section: Characterization Of Jscsupporting
confidence: 80%
“…Other peaks at JSC 1,377.17 cm À1 (C-N stretching vibration or amine), 1,273.02 cm À1 (vibrations of C-O stretching in alcohols), 987.55 cm À1 (C ¼ C stretching vibration), 844.82 cm À1 (C-H stretching vibration) were observed. Similar types of IR spectrum and functional groups were found by several authors (Chakraborty et al 2020;Ghosh et al 2021aGhosh et al , 2021b. The presence of a porous and uneven surface was indicated by using SEM analysis, which might have played a substantial role in providing high surface area and huge space for active sites (Figure 2).…”
Section: Characterization Of Jscsupporting
confidence: 80%
“…After each reaction, samples were centrifuged at 6000 rpm, and the concentration of residual dye present in the samples was determined by separating the supernatant and evaluating it using a UV-visible spectrophotometer at a wavelength of 594 nm by equation ( 4). [46] RB19 dye removal ð%Þ ¼…”
Section: Methodsmentioning
confidence: 99%
“…In this study, The F-value of the model is 54.65 which implies that the model for RB19 dye removal is significant. [5,46,47] Also, the adsorbent dosage had the majority significant effect with an F value of 626.69 followed by concentration (94.87), temperature (47.4), time (27.4), and pH (9.16).…”
Section: Anovamentioning
confidence: 99%
“…Research shows that the JS-activated carbon can be a solution to remove textile dyes (acid red-1, reactive orange-16, and methylene blue) from water by the adsorption process. 29 M. A. Aziz et al demonstrated that the carboxylated activated carbon from JS can be used to remove Pb 2+ ion from the aqueous solution. 30 G. C. Panda et al demonstrated that JS powder is a promising material for the adsorptive removal of Congo red and Rhodamine B from aqueous solutions.…”
Section: Introductionmentioning
confidence: 99%
“…29 M. A. Aziz et al demonstrated that the carboxylated activated carbon from JS can be used to remove Pb 2+ ion from the aqueous solution. 30 G. C. Panda et al demonstrated that JS powder is a promising material for the adsorptive removal of Congo red and Rhodamine B from aqueous solutions.…”
mentioning
confidence: 99%